Tracing the journey: Patient engagement in long-term antiretroviral therapy care in Malawi - Hannock Tweya; Agness Thawani; Robin Klabbers; Jacqueline Huwa; Ethel Rambiki; Evelyn Viola; Layout Gabriel; Geldert Chiwaya; Joseph Chintedza; Aubrey Kudzala; Christine Kiruthu-Kamamia; Pachawo Bisani; et al. (PLoS ONE, 2026)
Background Consistent engagement in antiretroviral therapy (ART) care is crucial to improve health outcomes and reduce HIV transmission. This study examined ART engagement patterns among ART clients during their first two years at two public ART clinics in Lilongwe, Malawi. Retention support for new initiates is provided by ART “Buddies” or through a two-way texting (2wT) system for those with phones and interest. Methods ART engagement patterns were assessed over six-month intervals (>0–6, > 6–12, > 12–18, > 18–24) among clients stratified by retention support group: 1) Buddy without phone access; 2) Buddy with phone access; and 3) 2wT. Outcomes were based on ART program status at the end of each interval. Clients were classified as retained on ART or not retained (lost to follow-up (LTFU), transferred out, stopped, or died). Among those retained, engagement was further categorised as continuously engaged (attended all appointments within 13 days), cyclically engaged (returned late (14–59 days) at least once, or re-engaged (missed an appointment by ≥60 days but returned to care). Clients were not censored within interval and could re-enter care in subsequent intervals. Results Among 6,303 clients, 5,880(93%) received ART Buddy support and 423(7%) received 2wT. Of those in the Buddy support group, 1,030 (18%) had phone access. 2wT clients showed the highest continuous engagement up to 18 months, compared to Buddy clients with and without phone access (70% vs 57% vs 30% at 0–6 months, 72% vs 58% vs 33% at >6–12 months, and 81% vs 76% vs 62% at >12–18 months). At 24 months, 3,363 (53%) were retained on ART: 2,790 (58%) of Buddy with phone; 277(27%) of Buddy without phone, and 296 (70%) of 2wT. Of those retained at 24 months, 1,834 (55%) were continuously engaged, 1,029 (31%) had cyclically engaged, and 500 (15%) re-engaged after LTFU across intervals. Conclusion ART engagement was dynamic and heterogeneous over time. Tailored retention support based on engagement patterns and time on ART could improve long-term retention in ART care.